Characterization of biogenic volatile organic compounds and membrane lipid peroxidation during leaf ageing in maize (Zea mays) - WANG, XINPING; TIU, TIANXUE; LI, CHAOHAI (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted to access BVOCs emission pattern during leaf senescence in parallel with monitoring leaf Chl degradation and MDA accumulation. BVOCs emission rate and Chl content of leaves in the lower canopy position were significantly lower than leaves in the mid and up positions. While MDA and H2O2 content of the lower position leaves were significantly higher than the up and mid position leaves. Positive correlation between leaf volatile emission rate and chlorophyll content and negative correlation between leaf volatile emission rate and MDA and H2O2 content were observed. VOCs emission pattern during the cereal crop aging could provide more evidence for age-related resistance though the results here we show are in vitro.